Highlighting Media & Journalism Futures 2030 : Survey on Weak Signals and Emerging Issues - Taylor, Amos; Heinonen, Sirkka; Ruotsalainen, Juho; Parkkinen, Marjukka (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2019)
In 2030 Media is undergoing a state of change becoming more customized toward individual, massive data driven and more intertwined within society. An emerging cross-cutting platform of diverse actors, with global access to media and information implies a much more complicated media culture. The meaning of a certain line of new journalism is enhanced. It is becoming more ethical, independent, collaborative, and networked, with better quality and better informed premises. Further, journalism riding in the same arena as gossip and automated information publication has to enhance its journalistic quality in order to differentiate itself and underline its authenticity. Individual authentic voice resonates while the journalistic ability is combined with editorial and production skills. Respondents’ answers in the survey cover many categories foreseeing the roles and functions of media and journalism where a democratic distribution of media content and access leads to a customised individualised media, “from 'us', to 'I'”. Moreover, new journalism is foreseen to emerge amidst a complex global networked culture. The MEDEIA research project anticipated new roles and functions for media in the emerging societal structure we call the Digital Meanings Society. It was carried out at Finland Futures Research Centre (FFRC), University of Turku during 2013–2015, and funded by the Media Industry Research Foundation of Finland, the Building Information Foundation, e21 Solutions, Teknologiainfo Teknova, Ministry of Transport and Communications and TeliaSonera.